Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.656
|View full text |Cite
|
Sign up to set email alerts
|

Queens are Powerful too: Mitigating Gender Bias in Dialogue Generation

Abstract: Social biases present in data are often directly reflected in the predictions of models trained on that data. We analyze gender bias in dialogue data, and examine how this bias is not only replicated, but is also amplified in subsequent generative chit-chat dialogue models. We measure gender bias in six existing dialogue datasets before selecting the most biased one, the multi-player textbased fantasy adventure dataset LIGHT (Urbanek et al., 2019), as a testbed for bias mitigation techniques. We consider three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 64 publications
0
91
0
Order By: Relevance
“…For dialogue, gender biases in training corpora have been found to be amplified in machine learning models Dinan et al, 2020;Liu et al, 2019). While many of the works cited above proposed methods of mitigating the unwanted effects of gender on text, Hall Maudslay et al ( 2019), Liu et al (2019), Zmigrod et al (2019), andDinan et al (2020) in particular relied on counterfactual data to alter the training distribution to offset gender-based statistical imbalances (see §4.2 for more discussion of training set imbalances). Also relevant is Kang et al (2019, PASTEL), which introduced a parallel style corpus and showed gains on style-transfer across binary genders.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…For dialogue, gender biases in training corpora have been found to be amplified in machine learning models Dinan et al, 2020;Liu et al, 2019). While many of the works cited above proposed methods of mitigating the unwanted effects of gender on text, Hall Maudslay et al ( 2019), Liu et al (2019), Zmigrod et al (2019), andDinan et al (2020) in particular relied on counterfactual data to alter the training distribution to offset gender-based statistical imbalances (see §4.2 for more discussion of training set imbalances). Also relevant is Kang et al (2019, PASTEL), which introduced a parallel style corpus and showed gains on style-transfer across binary genders.…”
Section: Related Workmentioning
confidence: 99%
“…By learning to associate control variables with textual properties, generative models can be controlled at inference time to adjust the generated text based on the desired properties of the user. This has been applied to a variety of different cases, including generating text of different lengths (Fan et al, 2018a), generating questions in chit-chat (See et al, 2019), and reducing bias (Dinan et al, 2020).…”
Section: Controllable Generationmentioning
confidence: 99%
See 3 more Smart Citations